1992
DOI: 10.1210/en.131.6.2659
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing hormone and adrenocorticotropic hormone concentrations in cerebrospinal fluid of dogs with pituitary-dependent hyperadrenocorticism

Abstract: There is still some controversy concerning the question of whether Cushing's disease in man is caused by a primary dysfunction of the pituitary or a hypothalamic disorder. In the latter option, excessive hypothalamic stimulation of pituitary corticotropes would cause or contribute to the genesis of POMC-secreting adenomas. In the present study cerebrospinal fluid (CSF) CRH levels and levels of ACTH and cortisol in CSF and plasma were measured in clinically healthy dogs, in dogs with pituitary-dependent hyperad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This is in concordance with results from earlier studies. In man and dog, it has been shown that the excessive ACTH secretion in Cushing's disease is not caused by persistent hyperstimulation of corticotropes by CRH (29,38), and canine ACTH-producing tumours have been shown to be relatively insensitive to stimulation by hypothalamic hormones in vitro (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in concordance with results from earlier studies. In man and dog, it has been shown that the excessive ACTH secretion in Cushing's disease is not caused by persistent hyperstimulation of corticotropes by CRH (29,38), and canine ACTH-producing tumours have been shown to be relatively insensitive to stimulation by hypothalamic hormones in vitro (39).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of PDH was based upon measurements of corticoid/creatinine ratios in urine before and after dexamethasone administration (28), measurements of plasma ACTH concentration (29) and computed tomography of the pituitary gland (30). Total hypophysectomy was performed by the trans-sphenoidal approach described by Markowitz et al (31), with slight modi®cations.…”
Section: Tissue Culturementioning
confidence: 99%
“…In the debate over possible ways to decrease the number of recurrences and over the early detection of surgical failure, corticotropic cell hyperplasia has played a confounding role. It was presumed to be due to excessive production of hypothalamic CRH but in recent years it has been demonstrated that CRH concentrations in cerebrospinal fluid of both humans (Kling et al 1991) and dogs (van Wijk et al 1992) with pituitary-dependent hyperadrenocorticism (PDH) are lower than in healthy individuals. Moreover, there is now increasing evidence that the disease originates at the pituitary level by clonal expansion of a single aberrant cell (Pei & Melmed 1996) and that corticotropic hyperplasia does not exist in Cushing's disease (Trouillas et al 1996).…”
Section: Introductionmentioning
confidence: 99%